THE INFLUENCE OF ECONOMIC LITERACY, FINANCIAL LITERACY AND SELF CONTROL ON CONSUMER BEHAVIOR AMONG SHOPEE USERS AMONG MUHAMMADIYAH UNIVERSITY STUDENTS IN SIDOARJO - Senja Putri Juanita; Fityan Izza Noor Abidin (Journal of Artificial Intelligence and Digital Economy, 2025)
Objective: This study aims to analyze the influence of economic literacy, financial literacy, and self-control on consumptive behavior among students. Method: The research was conducted on 117 final-semester students of the Accounting Study Program at Muhammadiyah University of Sidoarjo. Primary data were collected through questionnaires and analyzed using validity and reliability tests, multiple linear regression analysis, and hypothesis testing (t-test) with SPSS version 26. Results: The findings reveal that economic literacy and self-control have a significant positive effect on consumptive behavior, while financial literacy has a significant negative effect. Novelty: This study contributes to understanding how literacy and behavioral factors interact in shaping students’ financial decision-making, offering valuable insights for educators and policymakers to promote more responsible spending habits among young adults.